PELATIHAN PENGGUNAAN ECO-ENZYM UNTUK HIDROPONIK DAN NUTRISI PADA KOLAM IKAN - Puguh Sujarta; Suharno Suharno; I Made Budi (LPPM Uncen, 2023)
Eco-enzyme is a multifunctional liquid produced from the fermentation of waste or organic waste, brown sugar/sugar, and water. Eco-enzyme is a magic liquid whose benefits are very environmentally friendly, such as in the eco-enzyme production process to produce O3 gas (same as planting 10 trees), one liter of eco-enzyme solution can purify polluted rivers, like an antiseptic. and fertilize the soil. This activity has been carried out at SMA Negeri 2 Skanto in 2022, but now it is devoted to the use of eco-enzymes for hydroponics and fish pond nutrition. The purpose of this activity is to first introduce a training program on the use of eco-enzymes for hydroponics and fish pond nutrition; second, through service, it can produce output in the form of a national service journal. This activity was held on Juny 14, 2022 at SMA Negeri 2 Skanto Keerom. The target audience involved in this activity are high school students. The selection of the target audience is based on the tasks and obligations of students to build Adiwiyata High School that loves the environment. The methods used in the implementation of this activity are lectures, simulations and practice on how to harvest and use it. In conclusion, the participants were enthusiastic and knowledgeable about harvesting and using ecoenzymes. Based on the results of the evaluation showed that the level of satisfaction of participants was high when viewed from the percentage of all aspects.Keywords: antiseptic; eco-enzym; adiwiyata; keerom; hydroponic